A novel method in myocardial injury risk stratification using intravenous fat emulsion as sole rapid preparation for unfasted patients to suppress myocardial 18F-fluorodeoxyglucose uptake for optimal cardiac PET imaging: a proof-of-concept randomized-crossover trial - Li, Michael H-G.; Boktor, Raef R.; Rowe, Christopher; Weinberg, Laurence; Riedel, Bernhard (Frontiers in Nuclear Medicine, 2024)
Abstract Objectives: Optimal imaging of ischemic or inflammed myocardium via 18F-FDG PET imaging requires suppression of background carbohydrate metabolism in normal myocardium. Sole administration of intravenous lipid emulsion has not previously been used to rapidly prepare unfasted patients, such as in emergent clinical situations. In this proof-of-concept pilot, we posited that intravenous fat emulsion suppresses physiological metabolic uptake of in non-ischemic, non-inflammatory myocardium in unprepared and unfasted setting for enhanced cardiac positron emission tomography (PET) imaging. Methods: We conducted an ethics-approved, single-blind, prospective randomized crossover trial of 10 healthy volunteers from January 2020 to June 2021. Participants were unfasted and rendered hyperglycemic before being administered either high dose intravenous lipid emulsion—1.5mL kg of 20% lipid emulsion, followed by 15mL/kg/hr for 30mins—or saline prior to 18F-FDG injection and subsequent cardiac PET imaging. Assessors undertook image analysis for maximum standard uptake value (SUVmax), minimum standard uptake value (SUVmin) and qualitative assessment, and groups were compared using univariate analysis. Results: The study population age was 44.5 years [IQR 32.5–56.5], with 50% male and a median BMI of 22.75 [IQR 25.0–28.5] kg/m2. The study was feasible and there were no adverse side effects from the interventions. In these participants with normal myocardium, 18F-FDG uptake was significantly reduced by intravenous lipid emulsion as assessed by SUVmax and qualitative assessment (p = 0.042, r = 0.454 and p = 0.009, r = –0.581, respectively). Conclusions: Intravenous lipid emulsion suppresses background metabolic uptake of 18F-FDG even in unprepared and unfasted patients. Our findings prove and expand the possible applications for cardiac 18F-FDG PET in various settings, including in emergent settings as a means of rapid preparation in place of current more time-consuming standard protocols, allowing time-critical management to be effected.